1995
DOI: 10.1017/s0954579400006829
|View full text |Cite
|
Sign up to set email alerts
|

The Waterloo Longitudinal Project: Predicting internalizing and externalizing problems in adolescence

Abstract: We examined childhood social withdrawal and aggression as predictive of adolescent maladaption, comparing and contrasting social and emotional outcomes associated with aggression and social withdrawal. We also focused on childhood social competence as a predictor of adolescent adaptation. The sample comprised 60 children for whom a complete data set was available at both ages 7 and 14 years. The predictors were aggregated measures of social withdrawal, aggression, and social competence derived from three sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
217
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 262 publications
(242 citation statements)
references
References 47 publications
17
217
1
7
Order By: Relevance
“…Specifically, socially withdrawn children and young adolescents who are socially anxious and shy (that is, they passively withdraw from peers; Hymel, Rubin, Rowden, & LeMare, 1990) have negative self-perceptions of their social competence and their relationships, experience loneliness, and suffer from depressive symptoms (e.g., Boivin & Hymel, 1997;Gazelle & Ladd, 2003;Nilzon & Palmerus, 1998;Rubin, Chen, McDougall, Bowker, & McKinnon, 1995). Also, relative to nonwithdrawn children, young socially anxious, shy, withdrawn children are socially unskilled (e.g., Gazelle & Rudolph, 2004;Stewart & Rubin, 1995).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Specifically, socially withdrawn children and young adolescents who are socially anxious and shy (that is, they passively withdraw from peers; Hymel, Rubin, Rowden, & LeMare, 1990) have negative self-perceptions of their social competence and their relationships, experience loneliness, and suffer from depressive symptoms (e.g., Boivin & Hymel, 1997;Gazelle & Ladd, 2003;Nilzon & Palmerus, 1998;Rubin, Chen, McDougall, Bowker, & McKinnon, 1995). Also, relative to nonwithdrawn children, young socially anxious, shy, withdrawn children are socially unskilled (e.g., Gazelle & Rudolph, 2004;Stewart & Rubin, 1995).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…were stable between ages 7 years and 10 years (e.g., Hymel et al 1990;Rubin et al 1995). Data also revealed that approximately two-thirds of extremely socially withdrawn children maintained their status from ages 5 to 11 years across every 2-year period .…”
mentioning
confidence: 94%
“…Children characterized as socially withdrawn spend most of their time playing alone and on the periphery of the social scene, often due to shyness or social anxiety. Importantly, social withdrawal has been shown to be moderately stable from early through middle childhood (Hymel et al 1990;Rubin et al 1989Rubin et al , 1995 and from late childhood through early adolescence (e.g., Schneider et al 1998). For example, in the Waterloo Longitudinal Project, Rubin and colleagues reported that observed social withdrawal (the aggregate of [unoccupied onlooker solitary play] among familiar peers) was stable from ages 5 to 9 years and that peer perceptions of social withdrawal (peer nominations for such items as Someone who is shy and Someone who likes to play alone)…”
mentioning
confidence: 99%
See 2 more Smart Citations